The use of anonymous pop-quizzes (APQs) as a tool to reinforce learning - Le, Me-Linh (Journal of the Medical Library Association, 2012)
Doing the keyword search ''dental floss'' will find articles where: a) The words dental AND floss appear somewhere b) The words dental OR floss appear somewhere c) The words dental floss appear side-by-side Point of care tools (like DynaMed) provide the following: a) Summarized evidence on a topic b) Patient handouts c) Extensive references d) Treatment options e) a, b, and d f) All of the above Medical Subject Headings (MeSH) are a ''controlled vocabulary'' that lets you use one term to: [select all that apply] a) Capture variations in spelling b) Capture variations in language (e.g., French, Arabic) c) Capture variations in terminology After class, the instructor compared the number of completed quizzes with the number of students in the class to ensure all students had completed the quiz. Ultimately, the use of anonymous pop-quizzes in library instruction sessions provides an opportunity to engage students with an interactive component; test students' learning without accompanying test ''anxiety''; serve as an effective posttest if following a bridge, objective, pretest, participatory learning, posttest, summary (BOPPPS) or similar model; and allow the instructor to identity teaching areas of strength and weakness for future sessions.